Association of chromosome 5q21.3 polymorphisms with the exploratory eye movement dysfunction in schizophrenia - Ma, Yuanlin; Li, Jun; Yu, Hao; Wang, Lifang; Lu, Tianlan; Pan, Chao; Han, Yonghua; Zhang, Dai; Yue, Weihua (Scientific reports, 2015)
Schizophrenia patients show abnormalities in many eye movement tasks. Among them, exploratory eye movements (EEM) dysfunction seems to be specific to schizophrenia. However the mechanism of EEM disturbances in schizophrenia patients remains elusive. We investigate the relationship between EEM and single nucleotide polymorphisms (SNPs) or genes to identify susceptibility loci for EEM in schizophrenia. We firstly performed EEM test, then performed a genome-wide association study (GWAS) and gene-based association study of EEM in 128 individuals with schizophrenia and 143 healthy control subjects. Comparing to healthy controls, schizophrenia patients show significant decrease in NEF (22.99 ± 3.96 vs. 26.02 ± 5.72, P <0.001), TESL (368.78 ± 123.57 vs. 603.12 ± 178.63, P <0.001), MESL (16.86 ± 5.27 vs. 24.42 ± 6.46, P <0.001), RSS (8.22 ± 1.56 vs. 10.92 ± 1.09, P <0.001) and CSS (5.06 ± 0.97 vs. 6.64 ± 0.87, P <0.001). Five SNPs of the MAN2A1, at 5q21.3, were associated with EEM abnormalities (deceased CSS) and satisfied the criteria of GWAS significance threshold. One is localized near 5’-UTR (rs17450784) and four are in intron (rs1438663, rs17162094, rs6877440 and rs10067856) of the gene. Our findings suggest that the identified loci may control the schizophrenia-related quantitative EEM trait. And the identified gene, associated with the EEM phenotype, may lead to new insights into the etiology of schizophrenia.